Nilai-Nilai Pendidikan Agama Hindu Yang Terkandung Dalam Paribasa Bali Suguhan Pertunjukan Wayang Kulit Cenk Blonk - I Wayan Sugita; I Gede Tilem Pastika (Jayapangus Press, 2021)
The rapid globalization has caused the Balinese language (BB) to become extinct. If BB goes extinct, Paribasa Bali (PB) will also disappear. In fact, PB has various functions, including forming noble characters. Various groups including the government took various efforts to preserve PB. Among the artists, one of them who preserved PB was the puppeteer I Wayan Nardayana in the Wayang Kulit Cenk Blonk (WKCB) performance. The problems discussed in this study are (1). What form of PB is shown in the WKCB performance? (2). What is the function of PB that is shown in the WKCB performance? (3) What Hindu religious education values are contained in PB that is shown in the WKCB performances? To analyse these problems, some theories are used. Popular culture theory is used to analyse the form of PB, semiotic theory is used to analyse PB functions and critical discourse theory is used to analyse the values of Hindu religious education contained in the PB presented by WKCB performances. The results of the study are as follows: 1). The PB forms in WKCB performance are (1) sesonggan; (2) Cecangkitan; (3) bladbadan; (4) Sesenggakan; (5) Peparikan; (6) Cecimpedan; (7) Sesawangan. 2) The PB functions in WKCB performance, namely: (1) The function of giving advice; (2) The function of conveying ridicule; (3) The function of humbling oneself; (4) The function of delivering praise; (5) Entertaining function; (6) aesthetic function; (7) Function of conveying bad luck. 2) The value of Hindu religious education contained in WKCB's PB performance, namely: (1) The value of self-education; (2) The value of education protects the weak; (3) The educational value of tradition; (4) The value of education makes satvika; (5) The educational value of the Tri Kona; (6) the value of awareness about appearance education; (7) The value of education improves the quality of human resources.